Diagnostic pathology. Blood and bone marrow - Foucar, Kathryn (Salt Lake City : Amirsys Pub., 2012)
"Designed as an easy-to-use and comprehensive reference for the practicing pathologist, Diagnostic pathology: blood and bone marrow is the newest title in the Diagnostic pathology series by Amirsys. This extensively illustrated book showcases over 1,900 high-quality images, including gross pathology and a variety of pathology stains. Included are several images that display specialized immunophenotypic and molecular genetic features of bone marrow disorders. As readers have come to expect from Amirsys reference tools, the content is presented in concise, bulleted text that quickly gets to the most critical diagnostic data, including a variety of differential diagnoses. This book pinpoints important elements in the diagnosis of benign and neoplastic disorders and it clearly delineates numerous genetic disorders often found in blood and bone marrow. Diagnostic athology: blood and bone marrow is set to become a valuable reference resource for the busy pathologist"--Provided by publisher
Anemia -- Erythrocytes -- Benign leukocyte disorders in blood and bone marrow -- Constitutional granulocytic disorders -- Megakaryocytic disorders-- Infection -- Miscellaneous nonneoplastic disorders and conditions -- Myeloid neoplasms -- Acute leukemias of ambiguous lineage -- Lymphoid neoplasms -- Other neoplasms involving bone marrow -- Antibody index
Includes bibliographical references and indexes
Keywords: Blood -- Diseases -- Atlases; Hematologic Diseases -- pathology; Hematologic Diseases -- Atlases; Hematologic Diseases -- diagnosis